ENDOGENOUS INTOXICATION IN RATS AFFECTED BY HEXAVALENT CHROMIUM COMPOUNDS AND TUBERCULOSTATICS AFTER APPLICATION OF THIOTRIAZOLINE - Burmas, N.I.; Fira, L.S.; Bojko, L.A.; Kurtyak, B.M.; Vishchur, O.I. (World of Medicine and Biology, 2018)
Currently, the growing incidence of toxic lesions of the liver is associated with industrial chemicalization and uncontrolled use of hepatotoxic drugs in everyday life. Intoxication of the body by the different xenobiotics leads to the development of metabolic disorders, correction factors are used to eliminate them. The aim of work was investigate the effectiveness of the using of thiotriazoline in the organism of rats of different ages at the chromo-isoniazido-rifampicin affection. The experimental affection of rats of a different age was carried by the conditions of combined injection of hexavalent chromium compounds (a solution of potassium dichromate, 3 mg/kg), isoniazid (0,05 g/kg) and rifampicin (0,25 g/kg), which during 7th and 14th days injected antioxidant thiotriazoline (7 mg/kg). The experiments were conducted on outbred white male rats of three age groups: the 1st group – immature (3-month-old animals, 90-110 g in weight); 2nd group – mature (6-month-old animals, 150-170 g in weight); and the 3rd group – senile (18-months-old animals, 280-300 g in weight). All experimental animals of each age group were divided into three groups: 1th – control rats (injected with a physical solution); 2th – animals that were affected by the combined effect of K2Cr2O7, isoniazid and rifampicin; 3th – affected animals (the combined action of xenobiotics), which during the experiment was injected antioxidant tiotriazoline. Euthanasia was performed by means of thiopental sodium on the 7th and 14th days from the first day of xenobiotics administration. The study of liver homogenate and blood serum was performed.The activity of oxidizing processes was evaluated by the content of products of oxidation modification of proteins (2,4-DNPH). The severity of the endogenous intoxication syndrome was determined by the content of medium mass molecules (MMM) and the percentage of damage to the erythrocytic membrane (erythrocytic index of intoxication – EII). After the introduction of thiotriazoline, the content of free radicals decreases in the poisoned organism, which causes the destruction of membranes and the degradation of protein molecules, leading to the decreasing in the content of 2,4-DNPH of neutral and basic character, both in blood serum and in the liver of affected animals. After leading of thiotriazoline into the organism of affected animals, EII was decreased by 21 % in the immature animals at the 14th day of the experiment to the level of the affected animals, in the case of adult mature animals – by 30 %, in the senior animals – by 21 %. The research of the effect of used antioxidant was showed the normalization of the content of MMM in blood serum throughout all experiment. At the 7th day of the experiment, the content of MMM(254 nm) and MMM(280 nm) in immature animals decreased by 51 and 46%, at the end of the experiment – by 65 and 41%, respectively, in comparison with affected animals. At the researches in rats of different age groups, it was found that using antioxidant tiotriazoline there is a pronounced decrease the activity of free radical oxidation processes in animals of the sexually mature and mature age compared to the affected rats. It contributes to decrease the permeability of cell membranes (the percentage of damage to the erythrocytic membrane) and endogenous intoxication in the affected organism (the content of medium mass molecules).